Exploratory factor analysis and psychometrics properties of the Malay version Metacognitive Questionnaire 30 items - Mukhtar, Firdaus; Low, Jia Liang; Amdan, Siti Aisyah; Mardi, Maizura (Alicon Publications, 2018)
The Metacognitive Questionnaire-30 (MCQ-30) has been translated into many languages in different countries. The aim of the study was to determine the psychometric properties of Malay version of MCQ-30 (MCQ-30-M) among the undergraduate students in University Putra Malaysia. A cross sectional validation study was conducted on preclinical students in University Putra Malaysia (n=344). Participants completed a series of questionnaires that included MCQ-30-M, Depression, Anxiety, Stress Scale-21 (DASS21), and Automatic Thoughts Questionnaire. Using exploratory factor analysis, the MCQ-30-Malay was clustered into 5 factors in order to follow the original study which resulted in 2 factors that loaded with 3 questions and 5 items did not load to any factor. The MCQ-30-Malay demonstrated good internal consistency and moderate validity. The measures have shown moderate concurrent and convergent validity with other questionnaires that include Depression, Anxiety, Stress Scale-21 (DASS21), Automatic Thoughts Questionnaire-Malay (ATQ-M) and Sardinian Status Kesihatan Mental (SSKM). The measures also have shown a strong correlation between MCQ-30-M and its subscales. The findings of the study have shown that the MCQ-30-M has demonstrated good psychometric properties when being tested among preclinical student.